A Defense of Local People Working as Souvenir Vendors and Its Relation with the Female Identity in Kintamani Tourism Area, Bali - Ni Made Ary Widiastini; I Wayan Ardika; I Gede Mudana (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2018)
Souvenir vending is one of the jobs done by poor people in tourist areas such as Batur Tengah Village or better known as Penelokan, Kintamani, Bangli Regency, Bali to make their family survive. However, the souvenir vendors’ existence is not only considered by tourism businesses as unacceptable, but it is also regarded as a major factor that hampers the development of tourism in Kintamani. In fact, the Bali Local Regulation No. 2 of 2012 on Cultural Tourism explicitly emphasizes that the development of Bali’s tourism is aimed to encourage an equal distribution of business opportunities and to obtain maximum benefits for the welfare of the community. Therefore, this study was aimed to determine the reasons why the informal sector (souvenir vending) is used as the basis of the family economy, what is the practice of souvenir vending which has become the basis of the family economy, and also what is the struggle for vendor space in the Kintamani tourism area and its relation with the female identity. In this study, several techniques were used such as observations, interviews, and literature study to collect data. Research results show that the people in the Batur Tengah village choose to work as souvenir vendors because of their limited economic capital, education, skills, and time due to other life burdens, especially for those who are already married. In the Kintamani tourism area, souvenir vendors have to interact with various parties which certainly involves a capital struggle because each party has a different interest. As a famous international tourism area which has become a global Geopark, this area is highly contested for its economic, social, cultural, political, and environmental values. Researchers found a new paradigm that shows souvenir vending to be one form of entrepreneurship in a tourism field which is responded to by the people as a multi-purpose industry. The utilization of the informal sector is considered a family economic base by women in the village of Batur Tengah. Married woman are obligated to provide for their families hence they struggle as souvenir vendors in the middle of the tourism competition which has become more strict and less accommodative due to the new government policy. In practice, the community is very obedient to the elite community leaders who are considered as patrons, both by the men and women vendors. Other options to support their families are now very few and becoming less as the tourism areas are becoming more popular.